A 3 months clinical evaluation comparing two professional bleaching systems of 25% and 40% hydrogen peroxide and extended treatment outcome using a power versus a manual toothbrush. Issue 2 (26th November 2018) - Lee, Sean S.; Kwon, So Ran; Ward, Marilyn; Jenkins, Wendy; Souza, Sonia; Li, Yiming
Abstract: Objectives: To assess two professional tooth bleaching products: Philips Zoom WhiteSpeed (PZW) and Ultradent Opalescence Boost PF (UOB); and to assess bleaching maintenance after use of Philips Sonicare power toothbrush (SDC) or manual toothbrush (MTB). Methods: There was a randomized, parallel clinical trial. Eligible subjects were 18‐75 years, with VITA Classical shade (VCS) of A3 on anterior teeth. Subjects were randomized to bleaching with PZW or UOB. Tooth color and shade were assessed using VITA EasyShade (VES), VCS, and VITA Bleachedguide (VBG). Subjects returned on Days 7 and 30. On Day 30, participants were dispensed either SDC or MTB for home use until Day 90. Results: A total of 135 subjects completed the study. For the primary endpoint, ΔE at Day 7, a significantly larger reduction was observed for PZW than UOB ( P value = .0059). Significant differences in shade were also observed at Day 7 for VCS ( P value = 0.0106), and VBG ( P value = .0489). On Day 90, the SDC was statistically superior to MTB in maintaining shade per VBG and VCS, but not ΔE. Conclusions: At Day 7, PZW showed statistically greater change in overall color and shade than UOB. The SDC maintained tooth shade significantly better than MTB. Both bleaching regimens were safe. Clinical Significance: The outcomes confirm the bleaching efficacy advantage of a lower H2 O2 dose‐LED accelerated professional tooth bleaching system, compared to a higher‐dose H2 O2 approach. The safety assessments via clinical intraoral exam and daily logged use of subjects' desensitizing agents, and the incidence and severity of reported sensitivity, provide evidence that both professional products are safe for use. Finally, powered tooth brushing may confer an advantage to manual tooth brushing in maintaining tooth shade‐change results following professional whitening.